(3eUHGM GdOjGLi hZhK GdQGLi hcga GddGLi aj LHGfGJ eUQs - (3GHf Yjf GdaVdGA , eMeO Hf YHO Gddg GdfGSN, eLO GdOjf CHh GdeYGdjs ((3GdcJHNGfI s)
(3ChdgG (B:s
(3hHYO aEfg deG cGf ehdGfG GdhRjQ GdUGMH MQSg Gddg JYGdi s
(3BNQgG (B:s
(3hehdGfG GdUGMH GdhRjQ GdPi TgOJ CQHGH GdeedcI HaVdI s
(3HChdg agQSs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdOGf JjehQ (B87) s
Keywords: (3GdLZQGajG h GdHdOGfs